KREASI BANGUN RUANG DALAM PEMBELAJARAN MATEMATIKA BAGI PERSEKUTUAN ANAK DAN REMAJA (PAR) GKI MARTIN LUTHER SENTANI - Tiku Tandiangnga; Yuliana Yuliana; Rasmy Daud Dassi (LPPM Uncen, 2022)
GKI Martin Luther Sentani is one of the churches located in Sentani District, Jayapura Regency. GKI Martin Luther's congregation consists of four elements, one of which is the Children and Youth Association (PAR). From the results of discussions and interviews with several Sunday School teachers, information was obtained that the parents of Sunday School children complained when their children asked about lessons in formal schools, especially science subjects. When children offer assignments or homework from school, sometimes parents spontaneously asked the children to ask other people, especially assignments or homework for math subjects. of course, this problem is very important to find a solution considering that mathematics is a basic science. It is also known that Sunday School teachers are also often the place for Sunday School children to ask questions about assignments or homework from formal schools, especially about geometry. If faced with questions from Sunday School children about geometry, only some of sunday school teachers who can explain it. The explanation from the Sunday school teacher also sometimes makes children confused or difficult to understand what is explained. Taking into account the problems faced by Sunday School children, Sunday School teachers, in this case the PAR GKI Executive Board (BP) Martin Luther Sentani Church and the community service team, consider it necessary to hold activities that involve Sunday School children. The purpose of this activity is to inform or introduce geometry through concrete media as well as identifying the nature and elements of geometry and to hone Sunday school children's creations in learning about geometry through concrete media using paper and straws. Implementation of this service using several methods, that are the lecture, question and answer, and demonstrations. With this service activity, the participant’s knowledge about the concept or theory of geometry does not only come from textbooks but also through concrete media so that learning becomes fun. Apart from that, it sharpens the participant's creations in learning mathematics, especially in learning geometry.Keywords: mathematics learning; geometry; creation Jayapura